Differential Activation of Unconventional T Cells, Including iNKT Cells, in Alcohol‐Related Liver Disease. (10th April 2020) - Marrero, Idania; Maricic, Igor; Morgan, Timothy R.; Stolz, Andrew A.; Schnabl, Bernd; Liu, Zhang‐Xu; Tsukamoto, Hidekazu; Kumar, Vipin
Abstract : Background: Liver is enriched in several innate‐like unconventional T cells, but their role in alcohol‐related liver disease (ALD) is not fully understood. Studies in several acute alcohol feeding models but not in chronic alcoholic steatohepatitis (ASH) model have shown that invariant natural killer T (iNKT) cells play a pathogenic role in ALD. Here, we investigated the activation of iNKT cells in an intragastric (iG) infusion model of chronic ASH as well as the frequency and cytokine phenotype of 3 different unconventional T cells: iNKT, mucosal‐associated invariant T (MAIT), and CD8 + CD161 hi Vα7.2 − cells in peripheral blood of ALD patients. Methods: Hepatic iNKT cells were investigated using the iG model of chronic ASH that combines feeding of high‐cholesterol/high‐fat diet (HCFD) with intragastric feeding of ethanol diet (HCFD + iG Alc). Human iNKT, MAIT, and CD8 + CD161 hi Vα7.2 − cells were examined by flow cytometry in peripheral blood of patients with severe alcoholic hepatitis (SAH) and chronic alcoholics (ChA) and compared with healthy controls. Results: In the iG model of chronic ASH, IFNγ + iNKT cells accumulate in their livers compared with pair‐fed control mice and activated hepatic iNKT cells show high expression of Fas and FasL. Notably, IFNγ + iNKT cells are also significantly increased in peripheral blood of ChA patients compared with SAH patients. MAIT cells are significantly reduced in all ALD patients, but CD8 + CD161 hi Vα7.2 − cells are increased in SAH patients. Although MAIT and CD8 + CD161 hi Vα7.2 − cells displayed a similar cytokine production profile, the production of IFNγ and TNFα is significantly increased in SAH patients, while significant IL‐17A production is found in ChA patients. Conclusions: We found that the 3 unconventional T cells are activated in ALD patients showing interesting differences in their frequency and cytokine production profile between SAH and ChA patients. In the iG murine model of chronic ASH, iNKT cells are also activated secreting proinflammatory cytokines suggesting their involvement in liver disease. Abstract : Recently, a key pathogenic role for innate‐like, type I (iNKT) cells in the progression of alcoholic liver disease (ALD) has been shown in mice following oral alcohol‐feeding. Here, in intragastric chronic alcoholic steatohepatitis model, we show that hepatic iNKT cells produce significantly more IFN‐g and Fas/FasL. Consistently, proinflammatory iNKT cells are also chronically activated and produce higher IFN‐g/T‐bet but not IL‐4, in the blood of ALD patients suggesting their potential involvement. In contrast, MAIT cells are significantly depleted in these patients.